MODELLING OF GOLD MINERALIZATION ZONE IN EPITERMAL AREA USING RESISTIVITY, INDUCED POLARIZATION, AND MAGNETIC METHOD IN "CIMS" FIELD, GUNUNG PANI, POHUWATO DISTRICT, GORONTALO - Apriyanto, Fariz
"CIMS" Prospect Area, Gorontalo Province, is an area with low epithermal sulfide gold deposit types. The presence of gold in this area is associated with alteration minerals, especially sulfide minerals. In this study, an investigation was conducted to determine the distribution of prospect area for gold mineralization using the resistivity method, time domain Induced Polarization (IP), and airborne magnetic. The IP and resistivity methods are very suitable to be used to determine alteration areas in the epithermal system because they can detect sulfide and silica minerals properly. Measurement of IP and resistivity methods was carried out using a dipole-dipole configuration with 900 m line length and 50 m electrode spacing. The measurement area is divided into two blocks which are 350 m long with 9 lines per block with 100 m spaces between tracks. Airborne Magnetic method with ground clearence 60 m from topography used to detect reduction of magnetite effect in alteration zones of prospect area. The presence of mineralization is characterized by the presence of high chargeability anomalies (> 9 msec), high resistivity anomalies (> 260 Ohm.m), and low magnetic anomalies. After comparing the results of the three data with geological data, it can be concluded that the potential area for the presence of gold in the study area is very much controlled by the structure in the study area with elevations above 350 m.